2002
DOI: 10.1111/1468-2389.00198
|View full text |Cite
|
Sign up to set email alerts
|

The Big Five Personality Dimensions and Counterproductive Behaviors

Abstract: Little systematic research on personality measures has been directed at investigating whether the Big Five are predictors of counterproductive behaviors such as absenteeism, accidents, deviant behaviors, and turnover. For example, published meta-analyses did not investigate whether the Big Five personality factors predicted these criteria. The results of the meta-analyses carried out here showed that conscientiousness predicted deviant behaviors and turnover, and extroversion, openness, agreeableness and emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
511
9
26

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 626 publications
(574 citation statements)
references
References 43 publications
28
511
9
26
Order By: Relevance
“…Likewise, Mount et al (2006) found that agreeableness had a direct negative relationship with interpersonal counterproductive behaviors and job satisfaction partially mediated the relationship between agreeableness and workplace deviance. In addition, three meta-analytic results have shown agreeableness trait is negatively related to negative behavior in organizations (Berry et al, 2007;Dalal, 2005;Salgado, 2002). Consequently, the current study aims to extend the literature by further investigating the relationship between agreeableness and WDB.…”
Section: Agreeableness and Workplace Deviant Behaviormentioning
confidence: 93%
See 1 more Smart Citation
“…Likewise, Mount et al (2006) found that agreeableness had a direct negative relationship with interpersonal counterproductive behaviors and job satisfaction partially mediated the relationship between agreeableness and workplace deviance. In addition, three meta-analytic results have shown agreeableness trait is negatively related to negative behavior in organizations (Berry et al, 2007;Dalal, 2005;Salgado, 2002). Consequently, the current study aims to extend the literature by further investigating the relationship between agreeableness and WDB.…”
Section: Agreeableness and Workplace Deviant Behaviormentioning
confidence: 93%
“…On the other hand, some prior studies have shown conscientiousness is negatively related to deviant behavior in organizations Berry et al, 2007;Dalal, 2005;Salgado, 2002). For example, Farhadi et al (2011) carried out a pilot research on 162 employee of an organization to examine the predictor role of conscientiousness on workplace deviance.…”
Section: Conscientiousness and Workplace Deviant Behaviormentioning
confidence: 99%
“…In particular, we conduct an incentivized multiple price list (MPL) method of elicitation, in the style of Holt and Laury (2002 [2012]). Two of the "Big 5" personality traits have also found to be predictors of behavior (and of workplace performance): agreeableness and conscientiousness (Salgado [2002] and Mount et al [2006]). Other predictors include social value orientation, trait anger and negative a¤ectivity, self-control and locus of control (Hegarty and Sims [1978], Douglas and Martinko [2001], and Brizi et al [2015]).…”
mentioning
confidence: 99%
“…These indicate both constructs can be good predictors of performance, taking into account potential moderating effects (e.g., participants' occupation; Vinchur, Schippmann, Switzer & Roth, 1998). Several meta-analyses focusing on the personality domain have examined predictive validities for more specific criterion constructs than OJP, such as organizational citizenship behavior (Chiaburu, Oh, Berry, Li & Gardner, 2011;Hurtz & Donovan, 2000), job dedication (Dudley, Orvis, Lebiecki & Cortina, 2006) or counterproductive work behavior (Berry, Ones & Sackett, 2007;Dudley et al, 2006;Salgado, 2002). Hogan and Holland (2003) investigated whether differentiating the criterion-domain into two performance dimensions (getting along and getting ahead) impacts on predictive validities of personality constructs, using the Hogan Personality Inventory for a series of meta-analyses.…”
Section: Introductionmentioning
confidence: 99%